2023
DOI: 10.25646/11143
|View full text |Cite
|
Sign up to set email alerts
|

Health of people with selected citizenships: results of the study GEDA Fokus

Abstract: Background The health situation of people with a history of migration is influenced by a variety of factors. This article provides an overview of the health of people with selected citizenships using various indicators. Methods The analyses are based on the survey ‘German Health Update: Fokus (GEDA Fokus)’, which was conducted from November 2021 to May 2022 among people with Croatian, Italian, Polish, Syrian and Turkish citizenship. The prevalence for each health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 53 publications
1
5
1
Order By: Relevance
“…Since the differentiation of history of migration is specific to German health research, we refer to studies investigating the German population. Concordant, a longer duration of residence was found to be an important determinant of depressive symptoms and worse subjective health status, especially among men (14,37). Contrary to our expectations, the intersectional strata a priori defined as the most advantaged, namely males with no migration history and high income, only had the fourth lowest level of health anxiety.…”
Section: Summary Of Main Results and Discussion Of Current State Of R...contrasting
confidence: 95%
See 3 more Smart Citations
“…Since the differentiation of history of migration is specific to German health research, we refer to studies investigating the German population. Concordant, a longer duration of residence was found to be an important determinant of depressive symptoms and worse subjective health status, especially among men (14,37). Contrary to our expectations, the intersectional strata a priori defined as the most advantaged, namely males with no migration history and high income, only had the fourth lowest level of health anxiety.…”
Section: Summary Of Main Results and Discussion Of Current State Of R...contrasting
confidence: 95%
“…Against the background of low income as the most impactful of the three investigated social dimensions, our study revealed further evidence for the great importance of economic deprivation in light of other social characteristics such as history of migration (14). The relevance of socioeconomic disadvantage in health anxiety was also demonstrated in a recent meta-analysis (9).…”
Section: Summary Of Main Results and Discussion Of Current State Of R...supporting
confidence: 71%
See 2 more Smart Citations
“…Extensive research has been conducted on these migration related stress factors, assuming these stressors to represent significant risk factors for depression ( Berry, 2019 ; Foo et al, 2018 ; Gleeson et al, 2020 ). International meta-analytic data reveals a depression prevalence of 15.6% among migrants globally ( Foo et al, 2018 ), while recent German panel data indicates that 20.6% of migrant respondents reported depressive symptoms ( Bartig et al, 2023 ). Although the impact of the experience of migration on the mental health of migrants is evident ( Berry, 2019 ; Bhugra, 2004 ; Foo et al, 2018 ; Gleeson et al, 2020 ; Jannesari et al, 2020 ; Kluge et al, 2019 ; Metzing et al, 2020 ; Schwartz et al, 2010 ; ration on the mental health of migrants is Walther et al, 2020 ; WHO, 2022 ) the underlying processes are complex and remain insufficiently studied ( Balidemaj & Small, 2019 ; Berry, 2019 ; Bornstein, 2017 ; Choy et al, 2021 ; Foo et al, 2018 ; Kluge et al, 2019 ; Mesquita et al, 2019 ).…”
mentioning
confidence: 99%